Beneficial or Harmful Role of Macrophages in Guillain-Barré Syndrome and Experimental Autoimmune Neuritis - Donghui Shen; Fengna Chu; Yue Lang; Yunlong Geng; Xiangyu Zheng; Jie Zhu; Kangding Liu (Mediators of Inflammation)
Guillain-Barré syndrome (GBS), an immune-mediated demyelinating peripheral neuropathy, is characterized by acute weakness of the extremities and areflexia or hyporeflexia. Experimental autoimmune neuritis (EAN) is a common animal model for GBS, which represents a CD4+ T cell-mediated inflammatory autoimmune demyelination of the peripheral nervous system (PNS), and is used to investigate the pathogenic mechanism of GBS. It has been found that macrophages play a critical role in the pathogenesis of both GBS and EAN. Macrophages have been primarily classified into two major phenotypes: proinflammatory macrophages (M1) and anti-inflammatory macrophages (M2). The two different macrophage subsets M1 and M2 may play a decisive role in initiation and development of GBS and EAN. However, recently, it has been indicated that the roles of macrophages in immune regulation and autoimmune diseases are more complex than those suggested by a simple M1-M2 dichotomy. Macrophages might exert either inflammatory or anti-inflammatory effect by secreting pro- or anti-inflammatory cytokines, and either inducing the activation of T cells to mediate immune response, resulting in inflammation and demyelination in the PNS, or promoting disease recovery. In this review, we summarize the dual roles of macrophages in GBS and EAN and explore the mechanism of macrophage polarization to provide a potential therapeutic approach for GBS in the future.